2022
DOI: 10.1155/2022/5125931
|View full text |Cite|
|
Sign up to set email alerts
|

Implementation of Solar Heat Energy and Adsorption Cooling Mechanism for Milk Pasteurization Application

Abstract: The use of renewable energy is crucial to the global growth of sustainability. Milk business amongst many other food industry divisions requires a significant amount of energy, making the meal processing business one of the most energy-intensive industries. As of right now, more than 30 percent of the dairy produced in India is processed. In distant parts of India, milk spoiling is more common due to the delay among milking and storing; as a result, facilities for quick pasteurization and storage are needed. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Process electrification can lead to a gradual process decarbonisation, benefiting from the national or regional grid decarbonisation, in line with the net zero carbon target [18]. Process electrification can also lead to complete process decarbonisation when renewable energy is used directly to power the process [19]. Regarding the electrification of transportation, although fully electric refrigerated vehicles have not been currently released at scale, electric transportation is expected to be the dominant form of logistics in the future [20].…”
Section: Introductionmentioning
confidence: 99%
“…Process electrification can lead to a gradual process decarbonisation, benefiting from the national or regional grid decarbonisation, in line with the net zero carbon target [18]. Process electrification can also lead to complete process decarbonisation when renewable energy is used directly to power the process [19]. Regarding the electrification of transportation, although fully electric refrigerated vehicles have not been currently released at scale, electric transportation is expected to be the dominant form of logistics in the future [20].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%